Assessing the commercial potential of high-tech production business targets in risk-generated innovation economies using fuzzy set methods - Olha Ilyash; Vitaliy Zakharchenko; Svitlana Yermak; Larysa Frolova; Glib Mazhara; Liubov Smoliar (Business: Theory and Practice)
The purpose of the article is to develop a methodology that will make it possible to use attitudes and expressions of professional language to the maximum extent when selecting business goals of high-tech entrepreneurship during the development, production and sale of the latest products and to reduce the sensitivity of the assessment to small deviations of the factors and increase its reliability. It is proven that the proposed method allows to use the attitude and expression of professional language to the maximum when choosing a business goal. At the same time, the sensitivity of the assessment to small deviations of the factors decreases, and the reliability increases. It has been investigated and established that when using fuzzy methods in the decision-making process in high-tech production, unlike the existing ones, there is an opportunity to actively use fuzzy estimates and different points of view of people who carry out planning or decision-making, as well as fuzzy information expressed in words.